2012
DOI: 10.1007/978-94-007-4546-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Non-immediate Type Allergic Asthma due to Ammonium Persulfate

Abstract: While numerous cases of immediate-type occupational asthma due to persulfates with positive skin prick test reactions to ammonium persulfate are well documented, few non-immediate type reactions have been described in the literature. We report the case of an atopic worker who developed work-related asthmatic symptoms shortly after he began his job in persulfate production. The diagnosis of asthma was corroborated by methacholine testing. The patient showed a positive patch test reaction to ammonium persulfate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Some studies have observed a high level of exhaled NO in sensitized employees [70] or its increase after specific allergen challenge in sensitized employees [68,71,72]. The increase in exhaled NO has been observed 24-48 hours post allergen exposure in the working environment [68].…”
Section: Contribution Of Exhaled No Measurement In Occupational Asthmamentioning
confidence: 90%
See 1 more Smart Citation
“…Some studies have observed a high level of exhaled NO in sensitized employees [70] or its increase after specific allergen challenge in sensitized employees [68,71,72]. The increase in exhaled NO has been observed 24-48 hours post allergen exposure in the working environment [68].…”
Section: Contribution Of Exhaled No Measurement In Occupational Asthmamentioning
confidence: 90%
“…Néanmoins, l'ensemble des données disponibles suggère que la mesure de FE NO peut aider à identifier les asthmatiques non-observants parmi le sous-groupe ayant une valeur de FE NO initialement élevée.Apport de la mesure du NO expiré dans les asthmes en relation avec le travailDans le domaine de la recherche sur la santé respiratoire en milieu professionnel, la mesure de FeNO est de plus en plus souvent intégrée dans la batterie d'examens utilisés et a été réalisée chez des salariés de différents milieux professionnels : salariés exposés à des animaux de laboratoire, aux endotoxines, à des épices, aux isocyanates, au latex ou encore chez des agriculteurs, boulangers, personnel de soins, maîtres-nageurs[68][69][70]. Certaines études ont observé un niveau élevé de NO expiré chez des salariés sensibilisés[70] ou son augmentation après un test de provocation spécifique chez des salariés sensibilisés[68,71,72].L'augmentation du NO expiré a été observée de 24 à 48 heures après l'exposition aux allergènes du milieu professionnel[68]. D'autres études cependant, n'ont pas observé d'association entre la mesure de NO expiré et le résultat de tests de provocation bronchique spécifique ou la concentration en IgE spécifiques pour le latex, les diisocyanates et l'isocyanurate de triglycidyle[73,74] ou d'augmentation de la mesure de NO expiré avec l'augmentation de l'exposition au chrome et au cobalt[75].…”
unclassified
“…Lung function was recorded by body plethysmography [Criee et al, 2011] and spirometry [American Thoracic Society, 1995] with a MasterLab (Jaeger, Würzburg, Germany). Methacholine testing was performed with a reservoir method as described recently [Polychronakis et al, ]. The dose‐response relationship of this test is comparable to the American Thoracic Society's dosimeter test [Merget et al, ], but the delivered dose is documented as the dose at the mouthpiece, which is about half of the dose nebulized in the American Thoracic Society's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…All patients transferred to our outpatient clinic with suspected occupational asthma due to persulfate between 2003 and 2014 were included in this retrospective analysis (Patient 3 had been presented by Harth et al (2006), Polychronakis et al (2013) presented patient 6). All patients answered a questionnaire for medical history and underwent a physical examination, laboratory routine parameters including blood cell count, total immunoglobulin E (IgE), electrocardiogram, exhaled nitric oxide (eNO; Niox Mino, Aerocrine, Solna, Sweden), and X-ray of the thorax.…”
mentioning
confidence: 99%
“…The European Community for Steel and Coal (ECSC) reference values for spirometry were chosen . Methacholine testing was performed with a reservoir method as described by Polychronakis et al (2013). Bronchial hyperresponsiveness was assumed if (i) forced expiratory volume in 1 s (FEV 1 ) was reduced !20 % or (ii) specific airway resistance (sRt) doubled and increased to !2.0 kPa/s with a cumulative dose of 300 μg methacholine.…”
mentioning
confidence: 99%